Strategies for Fiscal Consolidation in the Post-Crisis World - Villafuerte, Mauricio (Departmental Papers; Departmental Paper ;, 2010)
In response to the global financial crisis, governments provided substantial support to the financial and other key sectors. Although this cushioned the adverse effects of the crisis, it is necessary now to articulate a strategy to ensure the sustainability of public finances. This paper discusses the scale and composition of fiscal adjustment that will need to occur once the recovery is securely under way. Although specific country-level circumstances will influence the composition of the adjustment and its political feasibility, in many cases restoring fiscal sustainability will require reforms to reduce spending and increase tax revenue.